Is Nephrolepis Faliciformis J. Sm. Evolving To Bipinnate Form? - RAVI PRATAP GAUTAM,; S. DOMINIC RAJKUMAR,; SHASHANK KUMAR SINGH,; SHOBHIT KUMAR SRIVASTAVA, (International Journal of Pharma and Bio Sciences, 2015)
Nephrolepis faliciformis J. Sm. is a very rare species found in tropical and humid regions of India. During many botanical explorations and from the cultivated plants in the St. Andrew’s College botanical garden N. faliciformis was found to be highly unstable in morphology. It was observed that this plant was evolving into a bipinnate form from simple pinnate form. This condition of instability in morphology exhibiting high degree of variations is discussed.